Europe's Dragonflies A Field Guide to the Damselflies and Dragonflies. - Smallshire, Dave (WILDGuides Ser., 2020)
The go-to photographic guide to all the damselflies and dragonflies recorded in Europe, including the Macaronesian Islands and western TurkeyEurope's Dragonflies is a comprehensive, lavishly illustrated and beautifully designed photographic field guide to the damselflies and dragonflies of Europe. Written by two well-travelled experts, the book covers all 140 resident and vagrant species recorded, focussing on the field identification of adult insects. Concise species profiles highlight key identification features and provide information on behaviour, habitat preferences, distribution, flight periods, status and conservation. Other sections cover identification tips, conservation status and legislation. Presenting an unsurpassed selection of images of the highest quality, this is the go-to guide for anyone wishing to know more about these amazing and fascinating insects.Comprehensive coverage of every species of damselfly and dragonfly recorded in EuropeStunning colour plates showing males, females, immatures, colour forms, subspecies and typical habitat for every speciesOver 1,200 superb photographs, supplemented with illustrations of fine detailsDetailed profiles for the 140 resident and vagrant speciesUnique comparison plates for difficult groupsEasy to use by beginners and experts alike, avoiding technical terms.